2018
DOI: 10.12890/2018_000817
|View full text |Cite
|
Sign up to set email alerts
|

Immune Thrombocytopenia Associated with Mycoplasma pneumoniae Infection

Abstract: Immune thrombocytopenia (ITP) related to Mycoplasma pneumoniae infection is a rare condition and usually associated with a severe clinical course. We here report a case of a young man with a clinical diagnosis of severe ITP secondary to M. pneumoniae infection. The clinical features, therapy and outcome are presented.LEARNING POINTSImmune thrombocytopenia (ITP) related to Mycoplasma pneumoniae infection is a rare condition.ITP secondary to M. pneumoniae infection appears to be associated with a more severe and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 11 publications
0
15
1
1
Order By: Relevance
“…On the contrary, ITP due to the M. pneumoniae infection belongs in the second group and this pathophysiology is less well understood. Potential mechanisms reported specifically for M. pneumoniae include platelet aggregation due to immune complexes, platelet clearance, and serotonin release [3]. Both Aviner et al and Gouveia et al reported cases and performed a literature report.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…On the contrary, ITP due to the M. pneumoniae infection belongs in the second group and this pathophysiology is less well understood. Potential mechanisms reported specifically for M. pneumoniae include platelet aggregation due to immune complexes, platelet clearance, and serotonin release [3]. Both Aviner et al and Gouveia et al reported cases and performed a literature report.…”
Section: Discussionmentioning
confidence: 99%
“…Both Aviner et al and Gouveia et al reported cases and performed a literature report. The former reported seven cases of ITP, while the latter reported 10 cases though there was some overlap [3,4]. Although the exact mechanism of ITP is unknown, some hypotheses are less likely based on the data from the case series performed by Aviner et al…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The latest discovery strongly indicated that a large number of MKs circulate through the lungs, where they dynamically release platelets, and an animal model showed that the lungs contributed approximately 50% of total platelet production in mice [3]. It is often observed that thrombocytopenia appears in patients with pulmonary diseases, such as pneumonia, chronic obstructive pulmonary disease (COPD) or respiratory failure (RF), which leads to major bleeding events and death [4][5][6][7]. However, whether pathophysiological state of lung affects platelets is unclear from both clinical and basic research information.…”
Section: Introductionmentioning
confidence: 99%
“…The latest discovery strongly indicated that a large number of MKs circulated through the lungs, where they dynamically released platelets, and an animal model showed that the lungs contributed approximately 50% of total platelet production in mice [3]. It is often observed that thrombocytopenia appears in patients with pulmonary diseases, such as pneumonia, chronic obstructive pulmonary disease (COPD) or respiratory failure (RF), which leads to major bleeding events and death [4][5][6][7]. However, whether pathophysiological state of lung affects platelets is unclear from both clinical and basic research information.…”
Section: Introductionmentioning
confidence: 99%